Pengaruh online customer review dan online customer rating terhadap minat pembelian pada pelanggan online shop bukalapak (studi pada pelanggan online shop bukalapak karyawan PT. Imexindo Intiniaga) - Hadi Joko Susanto; Muljadi Muljadi (Universitas Mercu Buana Yogyakarta, 2022)
The development of marketing is currently moving from traditional marketing to digital marketing, this has an impact on changing lifestyles and consumption patterns as well as the way people sell and shop. However, apart from the convenience that is obtained, there are also many factors that cause customers not to use the online shop, namely the problem of risk, which is generally related to security in payments, fear of fraud, or the quality of goods that do not meet expectations. The purpose of this study was to determine the effect of online customer reviews and online customer ratings on purchase interest in online shop customers of Bukalapak among employees of PT. Imexindo Intiniaga. The population in this study were employees of PT. Imexindo Intiniaga with a total of 232 employees, of which a sample was determined using the Slovin method technique, so a sample of 70 respondents was obtained. The results of this study are online customer reviews (X1) do not have a significant effect on purchase interest (Y) on Bukalapak online shop customers, online customer rating (X2) has a significant effect on purchase interest in Bukalapak online shop customers (Y).